Лучшие сказки про животных: коллекционное издание сказок : 0+ / ил. И. Есаулов - Есаулов И. (РООССА, 2011)
Экземпляры: ф.15 (20141113) / Инвентарный номер: 56234 / Цена: / Сис.шифр: 82.3(0) / Авт.знак: Л 87 / ГРНТИ: 17.71.07 / ББК: 82.3(0)